2022
DOI: 10.1186/s12891-021-04857-7
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic-assisted radiocarpal ligaments tensioning for dynamic radiocarpal instability

Abstract: Background Dynamic radiocarpal instability is one of the causes of post-trauma radial-sided wrist pain. It is not easy to diagnose and may possibly be overlooked. The key ligaments responsible for dynamic radiocarpal instability are the radioscaphocapitate (RSC) and long radiolunate (LRL) ligaments. Tensioning of these 2 ligaments could be a method of treatment for dynamic carpal instability. We proposed a method for arthroscopic thermal shrinkage of these 2 ligaments, and for setting a landmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…9 Although thermal shrinkage is also believed to facilitate ligament strengthening, this reinforcement by suture possibly provides more tightening compared with thermal shrinkage. 10,11 Additionally, the suture induces a fibrotic healing that probably will enhance the stability on the longer term. Esenyel et al demonstrated that nonabsorbable suture materials induces capsular reaction, with most of the inflammatory reaction in the first 3 to 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although thermal shrinkage is also believed to facilitate ligament strengthening, this reinforcement by suture possibly provides more tightening compared with thermal shrinkage. 10,11 Additionally, the suture induces a fibrotic healing that probably will enhance the stability on the longer term. Esenyel et al demonstrated that nonabsorbable suture materials induces capsular reaction, with most of the inflammatory reaction in the first 3 to 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…as well that a radial styloid resection should be performed only distal to the origin of the radioscaphocapitate ligament (i.e. level A) to avoid instability of the wrist presented as radial wrist pain and/or ulnar carpal (prosthetic) dislocation tendency [52,71,72]. A novel approach in order to enhance the stability of the radial-sided screw could be cement augmentation of it.…”
Section: Titanium Compression Screws (White Arrow A2) At the 1-year F...mentioning
confidence: 99%